Extrinsic calibration between multiple long baseline 4D mmWave radars for V2X - Yang, Zihan (Nanyang Technological University, 2024)
4D mmWave Radar(x, y,z, velocity), as a new sensor, possesses significant potential. Compared to LiDAR, it boasts advantages such as longer distance ranging, lower cost, and greater accuracy in adverse weather conditions. However, as a key aspect of multi-radar fusion, there is a scarcity of research on the extrinsic calibration of long baseline multi-radar systems. The main reasons can be summarized in three aspects: 1) As a new type of sensor, 4D radar has entered the market relatively recently. 2) Existing studies mostly focus on short baseline scenarios such as unmanned vehicles, with little attention given to long baseline and large viewpoint difference scenarios. 3) The point cloud from 4D radar is sparse and noisy, thus it is challenging to locate the target and extract the feature. To solve these problems, LB-R2R-Calib is proposed.